Pengaruh Operating Cash Flow, Profitabilitas, dan Leverage terhadap Financial Distress pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2018-2022 - Sintia Oktapani; Neni Maryani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The objective of this study is to investigate the impact of operating cash flow, profitability, also leverage on financial difficulties among property also real estate firms listed on the Indonesian stock exchange (IDX) from 2018 to 2022. This research employs quantitative methods, utilizing secondary data sources such as annual also financial reports obtained from 47 property also real estate companies during the specified period. The sampling procedure involved purposive sampling, yielding a total of 235 data samples. The research framework adopts multiple linear regression analysis. Findings from this investigation reveal that, individually, operating cash flow also profitability do not significantly influence financial distress, whereas leverage exhibits a detrimental effect. Moreover, collectively, operating cash flow, profitability, also leverage jointly impact financial distress within the realm of property also real estate enterprises listed on the Indonesian stock exchange (IDX) during the 2018-2022 period.